The Influence of Spinning Wheel Media and Module on The knowledge and Attitude of Adolescent Marriage Age Maturation at Bengkulu - Elvi Destariyani; Yuniarti Yuniarti; Nispi Yulyana (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Early marriage, according to the WHO, is a marriage that occurs in individuals under the age of 19. This phenomenon is often caused by a lack of knowledge and insufficient information about the importance of delaying marriage until an appropriate age. The impacts of early marriage include premature birth, delivery complications, divorce, domestic violence, school dropout, and other social problems. The aim is to determine the influence of spinning whell media on the knowledge and attitude of adolescent marriage age maturation. This study uses a Quasi-Experimental method with a Two Group Pretest and Posttest design. The research sample was taken using simple Random Sampling, involving 32 respondents who were given pretest and posttest questionnaires. The normality test used the Shapiro-Wilk test, and non-normal data were analyzed using the Mann-Whitney test. The results showed that the group receiving education through Spinning Wheel media experienced a significant increase in knowledge (average before 5.81, after 13.16) and attitudes (average before 39.00, after 52.94). Meanwhile, the group receiving education through Modul also showed an increase, though to a lesser extent, with an average knowledge score before 7.50 to 11.63 and an attitude score before 43.53 to 48.22. Statistical analysis showed a significant influence of education through Spinning Wheel media on improving adolescents' knowledge (p-value=0.000) and attitudes (p-value=0.000) about the maturity of marriage age. The findings of this study are expected to encourage academics, educational institutions, and other researchers to use Spinning Wheel media and develop other game-based learning methods to improve adolescents' knowledge and attitudes about the maturity of marriage age Keywords: Knowledge, Attitude, Early Marriage, Spinning Wheel Game, Adolescent Health.